Influence of dietary tryptophan to large neutral amino acids ratios on performance and well-being of broiler chickens subjected to stressful conditions - Bello, AlHassan Usman (2016)
Chickens in modern intensive production systems may suffer from multiple stress factors such as heat, handling, and transportation. These stressors are known to be negatively affecting welfare and well-being status of chickens. In search for a practical approach to alleviate the adverse effects attributed to such stressors, two experiments were conducted. The experiments were aimed to use conventional parameters together with novel and advance physiological and biotechnological measurements. In experiment 1, the influence of dietary tryptophan to large neutral amino acids ratios (TRP/LNAA) on performance, serotonin (5-HT), corticosterone (CORT), thyroxine (T4) and triiodothyronine (T3) of broiler chickens raised under high environmental temperature from 28-42 d were investigated. A total of 576 day-old male chicks were assigned to two controlled environments. Chicks in half of the chambers were challenged to cyclic high ambient temperature (35±1°C, 8h daily; heated), and the other half were kept at thermoneutral temperature (25±1°C; unheated). Birds were fed using six diets with ascending levels of dietary TRP/LNAA (0.025, 0.030, 0.035, 0.040, 0.045, and 0.050). Performance parameters were measured on a weekly basis. Blood samples were collected at the end of the experiment (42 d). The 5-HT, CORT, T3 and T4 were measured in the serum. The results revealed that irrespective of environmental condition, dietary TRP/LNAA had no influence on performance. However, dietary TRP/LNAA level has markedly affected the physiological responses of the birds. Evidently, elevation of TRP/LNAA coincided with reduction in CORT and increase in 5-HT, T3 and T4 (P<0.05). Increased 5-HT and reduced CORT are clearly indicating a superior welfare and well-being in TRP supplemented birds. In the follow up experiment, the effects of much higher dietary TRP/LNAA (0.050, 0.100, and 0.150%) was tested in broiler chickens receiving different types of pre-slaughter handling followed by transportation. A total of 180 d-old broiler chickens was fed using three dietary TRP/LNAA levels (0.050, 0.100, and 0.150). On day 42, birds were subjected to catching and handling in either short distance (25 meters) or long distance (100 meters) through the house. Blood, breast muscle and cecal samples were collected after 2 h of road transportation from all the birds. The results showed that increasing dietary TRP/LNAA improved FI and meat quality (drip loss and shear force) in broiler chickens and shifted the balance of pathogenic/non-pathogenic bacteria to a favorable state. Chickens fed higher levels of TRP/LNAA showed superior welfare condition as measured by lower HSP70 and higher 5-HT. Pre-slaughter long handling had minimal adverse effects on broiler chicken welfare condition and meat quality. Putting the data together, elevation of dietary TRP/LNAA is recommended as a practical measure to alleviate the adverse effects of stress on well-being of broiler chickens under stressful conditions.